Extraction, purification, biological effects and applications of acrosin: a review - Run Quan; Xiaolong Wu; Junjie Zhang; Rongxu Liu; Jianchun Han; Jianchun Han; Danyi Liu (Frontiers in Cellular and Infection Microbiology)
Acrosin is a proteolytic enzyme in the sperm acrosome that can stimulate sperm to penetrate the zona pellucida, causing the fertilization of the oocyte. Its activity is a crucial indicator of the sperm’s fertilization ability, which is critical in mammalian and human reproduction. However, there exists a lack of a comprehensive review of acrosin. In this study, we compared the extraction methods of acrosin, including acid extraction, buffer extraction, and saline extraction. The main methods for purifying acrosin, such as ammonium sulfate precipitation, ultrafiltration, dialysis, gel filtration chromatography, ion-exchange chromatography, and affinity chromatography, are reviewed. In addition, a detailed overview of the biological functions, inhibitors and applications of acrosin are outlined. This study provides methods for the extraction and purification of acrosin and some theoretical basis for the study of its properties. This provides a reference for further research on acrosin.